Kandungan Gizi Dan Keamanan Ikan Konsumsi Dari Pasar Tradisional Dan Modern - Verawati (CV. SINAR HOWUHOWU, 2025)
Fish is an important source of animal protein rich in essential nutrients such as protein and omega-3 fatty acids. However, the safety of fish consumption is a major concern due to potential contamination by heavy metals and pathogenic bacteria. This study aims to analyze the differences in nutritional content and safety levels of edible fish obtained from traditional and modern markets. Samples of Nile tilapia, catfish, and skipjack tuna were purposively collected from both market types and analyzed for protein, fat, omega-3 content, heavy metal concentration, and microbiological contamination using standard laboratory methods. The results indicate that fish from modern markets have slightly higher protein and omega-3 levels, while fish from traditional markets exhibit higher levels of heavy metal and bacterial contamination. These findings underscore the need for improved supervision and sanitation standards in traditional markets to ensure food safety. This study provides valuable information for consumers and policymakers in selecting and managing safe and high-quality fish for public health.